Strategi Penanganan Politik Uang Dalam Pemilu Legeslatif Berdasarkan Demokrasi Pancasila Menuju Pemilu Yang Berintegritas (International Forum of Researchers and Lecturers, 2024)
This article discusses strategies for handling money politics in legislative general elections using the Pancasila Democracy approach as a foundation for general elections with integrity. By referring to the principles of Pancasila which emphasize social justice, people's sovereignty,unity and balance between rights and obligations, this article identifies concrete steps that can be taken to overcome the practice of money politics which undermines democracy. Writing is carried out using normative juridical methods, namely research on secondary data or library materials. To realize elections with integrity, primary legal materials will guide the writing of strategies for handling political money in legislative elections based on Pancasila democracy. These steps include law enforcement, political education, financial transparency, independent oversight, active participation, public disclosure of the campaign, and use of technology. By implementing these strategies holistically and based on Pancasila values, it is hoped that Indonesia can overcome the challenges of money politics and strengthen integrity in the legislative election process, as well as build a stronger foundation for a healthy democracy and integrity.